Differences in muscle energy metabolism and metabolic flexibility between sarcopenic and nonsarcopenic older adults. Issue 2 (17th February 2022) - Shoemaker, Marni E.; Pereira, Suzette L.; Mustad, Vikkie A.; Gillen, Zachary M.; McKay, Brianna D.; Lopez‐Pedrosa, Jose M.; Rueda, Ricardo; Cramer, Joel T.
Abstract: Background: Metabolic flexibility is the ability of skeletal muscle to adapt fuel utilization to the demand for fuel sources [carbohydrates (CHO) and fats (FAT)]. The purpose of this study was to explore muscle energy metabolism and metabolic flexibility under various conditions in sarcopenic (S) versus nonsarcopenic (NS) older adults. Methods: Twenty‐two older adults aged 65 years or older were categorized as NS [ n  = 11; mean ± standard deviation (SD); age = 73.5 ± 6.0 years (males, n  = 5; females, n  = 6)] or S [ n  = 11; 81.2 ± 10.5 years (males, n  = 6; females, n  = 5) based on handgrip strength, body composition and physical performance. Indirect calorimetry was recorded before and after consumption of a high‐CHO meal and during aerobic and anaerobic exercise. Respiratory quotient (RQ), CHO and FAT oxidation were assessed. Venous blood samples were collected for glucose and insulin concentrations. Results: At rest, compared with NS, S exhibited a 5–8% higher RQ at 0 (0.72 vs. 0.76) and 120 (0.77 vs. 0.82), 150 (0.76 vs. 0.80), and 180 min (0.74 vs. 0.80) ( P  = 0.002–0.025); 59–195% higher CHO oxidation at 0, 120, and 180 min (0.0004–0.002 vs. 0.001–0.002 g·min −1 ·kg ‐1) ( P  = 0.010–0.047); and 20–31% lower FAT oxidation at 0, 15, and 90–180 min (0.0009–0.0022 vs. 0.0011–0.002 g·min −1 ·kg −1 ) ( P  = 0.004–0.038). Glucose levels were significantly elevated in S versus NS at 0, 60 and 75 min (144.64–202.78 vs. 107.70–134.20 mg·dL −1 ) but not insulin. During aerobic exercise, RQ was 5% greater (0.90 vs. 0.86) ( P  = 0.039), and FAT oxidation was 35% lower at 6–8 min (0.003 vs. 0.005 g·min −1 ·kg −1 ) ( P  = 0.033) in S versus NS. During anaerobic exercise, CHO oxidation was 31% greater in NS versus S at 60–80% time to exhaustion (0.011 vs. 0.007 g·min −1 ·kg −1 ) ( P  = 0.015). Per cent contribution to energy expenditure was greater in S for CHO but lower for FAT at 0 (CHO: 22% vs. 10%; FAT: 78% vs. 91%) and 120–180 min (CHO: 35–42% vs. 17–25%; FAT: 58–65% vs. 75%–84%) ( P  = 0.003–0.046) at rest and 6–8 min during aerobic exercise (CHO: 70% vs. 57%; FAT: 30% vs. 45%) ( P  = 0.046). Conclusions: The data show differences in skeletal muscle energy metabolism and substrate utilization between S and NS at rest, transitioning from fasted to fed state, and during exercise. Compared with NS, S displayed a diminished ability to adapt fuel utilization in response to feeding and exercise, reflecting metabolic inflexibility. Impaired metabolic flexibility could be a mechanism underlying the losses of strength and physical function accompanying sarcopenia.